Binomial expansions modulo prime powers - Paul W. Haggard; John O. Kiltinen (International Journal of Mathematics and Mathematical Sciences)
In this note a result is given and proved concerning binomial expansions modulo prime powers. In the proof congruence modulo prime powers is generalized to the rational numbers via valuations.